P1314 A singular explanation of stroke in young adults. (17th January 2020) - Campos, I; Azevedo, P; Costeira Pereira, A; Salome, N; Vieira, C; Pereira, V H; Costa Oliveira, C; Marques Pires, C; Medeiros, P; Flores, R; Mane, F; Mare, R; et al.
Abstract: INTRODUCTION: Although primary cardiac tumors are rare, papillary fibroelastoma (PFE) is the most common benign neoplasm of cardiac valvular structures. Because patients are often asymptomatic the true prevalence is unknown, being most commonly recognized given the evolution of higher-resolution imaging technology. The clinical presentation of PFEs can diverge between being asymptomatic to symptomatic based on the serious complications that can occur, such as acute valve dysfunction or embolization, giving rise to a wide variety of presenting features including neurologic events, acute coronary syndrome, and distal embolic events. The location on the mitral valve does not occur frequently, with rare cases reported in the literature. Here, we present an unusual case of a 32-year-old male with an acute stroke secondary to a PFE in the mitral valve. CASE REPORT DESCRIPTION A 32-year-old male patient with a history of crohn"s disease was admitted to our emergency department with a transient sudden-onset aphasia associated with a right hemiparesis. At admission, these symptoms had completely resolved. On further questioning, the patient described another episode of transient right hemiparesis in the last year. On physical examination, the patient"s vital signs were stable. The patient was awake, alert, and oriented with full Glasgow Coma Scale. There was no focal neurological deficit on neurological examination and his cardiovascular examination was normal with no murmurs, added sounds or carotid bruit. A cranial CT showed no signs of acute intracranial disease. Head MRI showed multiple areas of restricted diffusion in the left frontal lobe consistent with acute stroke. As part of the workup to determine the cause of his embolic stroke, a transthoracic echocardiogram and transoesophageal echocardiography were performed, showing a spherical and highly mobilemass attached on the downstream side of the anterior mitral valve leaflet of approximately 1.1 cm in diameter, suggesting the diagnosis of PFE. A bubble study was negative which out ruled patent foramen ovale. After completing the rest of the workup, it was determined that PFE was likely the cause of his stroke. Cardiothoracic surgery was consulted and the patient underwent surgical resection. Histology confirmed the diagnosis of PFE. After 5 years the patient remains asymptomatic, without new embolic events. DISCUSSION AND CONCLUSIONS We present a special case that illustrates the importance of diagnosing primary cardiac tumours in a young patient presenting with acute stroke with minimal or no risk factors.Although primary cardiac tumours are rare, diagnosis and treatment at an early stage may prevent serious complications and reduce the morbidity and mortality of embolic stroke.